Molecular mechanisms underlying the early steps of floral initiation in seasonal flowering genotypes of cultivated strawberry - Ziegler, Freya Maria Rosemarie; Gaston, Amelia; Guy, Karine; Devers, Marie; Krüger, Erika; Brauksiepe, Bastienne; Eimert, Klaus; Osorio, Sonia; Denoyes, Béatrice; Usadel, Björn (Frontiers in Plant Science, 2025)
Floral initiation is essential for sexual reproduction in angiosperms and plays a critical role in determining crop yields. In cultivated strawberry, however, the molecular mechanisms underlying floral initiation remain poorly understood, with most studies focusing on a single genotype under controlled conditions. To gain more insight into this process, we conducted a field-based study in two countries using two seasonal flowering cultivars. Our investigation focused on the early stages of floral initiation, analyzing samples that captured key developmental stages of the shoot apical meristem. Differential gene expression analysis of leaf and terminal bud tissues revealed an enrichment of genes involved in carbohydrate metabolism and phytohormone signaling pathways in leaves. Additionally, we observed enrichment of protein classes related to cytoskeleton organization, cell cycle regulation, and chromatin structure during early floral initiation. We also identified genes associated with the photoperiodic pathway, including well-known floral integrators such as TFL1 and SOC1, along with several other genes linked to phytohormone regulation, such as XTH23, PP2 and EIN3.